Pengembangan Agribisnis dan Nilai Tambah Kopi Melalui Skala Rumah Tangga Petani - Albina Munthe (Jurnal Visi Pengabdian Kepada Masyarakat, 2020)
The agricultural product that had emerged in the village of pardomuan motung the ajibata district was the coffee. Among the problems that coffee farmers have faced in this area are the decline in coffee production over the past few years and that farmers have a knowledge of the processing and improvement of coffee. The goal of this activity is to improve the knowledge and skills of the group of tanal-coffee and coffee processing as previews of the region. In turn, it enhances the quality and quality of the coffee and the appeal of the product to a high competitiveness. Strengthen community business groups so as to provide income for the people around them.